Study on Mechanical Effect and Plastic Zone Distribution of Tunnel Surrounding Rock in the Presence of Various Expansion Approaches - Bowen Duan; Jun Yang (Advances in Civil Engineering)
To examine the distribution of the plastic zone of the surrounding rock subjected to various expansion approaches used for the existing tunnels, this article deals with the distribution and thickness of the plastic zone of the surrounding rock subjected to one-sided expansion excavation (1SEE), two-sided expansion excavation (2SEE), and surrounding expansion excavation (SEE). First, the mechanical model of tunnel expansion is established and the initial stress field 1SEE and expansion stress field of tunnel surrounding rock are analyzed. The finite element model of tunnel expansion is developed to examine the plastic zone distribution in the presence of various tunneling approaches. The obtained results reveal that with the growth of expansion size, the plastic distribution area grows, with a maximum increase rate of 138.5%; the difference of each position reduces, with the difference value of each part less than 0.2 m. The plastic zones of 2SEE and SEE approaches are almost symmetrically distributed around the tunnel center line, and the invert and vault of the SEE tunnel are excavated at the same time, the excavation size is the same, and the difference in plastic zone range is small. With the rise of the lateral pressure coefficient, the distribution pattern of the plastic zone changes from X-type to butterfly-type and then to ellipse-type.